A Machine-Learning History of English Caselaw and Legal Ideas Prior to the Industrial Revolution II: Applications - Peter Grajzl; Peter Murrell (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This is the second of two papers that generate and analyze quantitative estimates of the development of English caselaw and associated legal ideas before the Industrial Revolution. In the first paper, we estimated a 100-topic structural topic model, named the topics, and showed how to interpret topic-prevalence timelines. Here, we provide examples of new insights that can be gained from these estimates. We first provide a bird's-eye view, aggregating the topics into fifteen themes. Procedure is the highest-prevalence theme, but by the mid-18th century attention to procedure decreases sharply, indicating solidification of court institutions. Important ideas on real-property were substantially settled by the mid-17th century and on contracts and torts by the mid-18th century. Thus, crucial elements of caselaw developed before the Industrial Revolution. We then examine the legal ideas associated with England's financial revolution. Many new legal ideas relevant to finance were well accepted before the Glorious Revolution. Finally, we examine the sources of law used in the courts. Emphasis on precedent-based reasoning increases by 1650, but diffusion was gradual, with pertinent ideas solidifying only after 1700. Ideas on statute applicability were accepted by the mid-16th century but debates on the legislature's intent still occurred in 1750.
Keywords: C80; N00; K10; K43; O43; 330; English history; institutional development; caselaw; financial revolution; sources of law